San Félix de Torralba de Ribota; Geometric Characterization of Fortified Churches (diségno, 2018)
In the mid 14th century, between 1356 and 1369, during the so-called “War of the two Peters” in Spain, small churches were built in a series of border enclaves, such as the Church of Santa María in Tobed, the one of San Martin in Morata de Jiloca and San Felix in Torralba de Ribota. Those churches would form part of a new typology called Fortified Churches, “because of their strong military character, provided by their compact external volumes, and their towers-buttresses” [Borras Gualis 2006]. The aim of research is the formal definition of an architectural typology with a high level of heritage interest. Virtual construction, through the combination of photogrammetric and laser scanning techniques, made it possible to achieve an accurate survey on which to make graphic analyses with the required precision, thereby obtaining the regulatory outlines used for the architectural design of the building. The precision obtained is of great interest in characterizing the shape, especially the curvature of the arches, the plements and other non-rectilinear elements, in order to generate a comparable database.
Keywords: Mediterranean Gothic; Strength-Churches; Laser Scanner; Photogrammetry; Geometric characterization arcs